2019
DOI: 10.1073/pnas.1821045116
|View full text |Cite
|
Sign up to set email alerts
|

sGC stimulator praliciguat suppresses stellate cell fibrotic transformation and inhibits fibrosis and inflammation in models of NASH

Abstract: Endothelial dysfunction and reduced nitric oxide (NO) signaling are a key element of the pathophysiology of nonalcoholic steatohepatitis (NASH). Stimulators of soluble guanylate cyclase (sGC) enhance NO signaling; have been shown preclinically to reduce inflammation, fibrosis, and steatosis; and thus have been proposed as potential therapies for NASH and fibrotic liver diseases. Praliciguat, an oral sGC stimulator with extensive distribution to the liver, was used to explore the role of this signaling pathway … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 32 publications
3
45
1
Order By: Relevance
“…In addition, Schwabl et al, using another sGC stimulator (riociguat), described reductions in portal hypertension and liver fibrosis in cholestatic (bile duct ligation) and toxic (carbon tetrachloride; CCl 4 ) models of cirrhosis in rats (4). More recently, Hall et al confirmed the antiinflammatory and antifibrotic effects of PRL in different murine models of NASH, including CCl 4 , streptozotocin plus a high-fat/high-cholesterol diet, and thioacetamide (5). Together, the findings of these studies position the cGMP pathway as a new and promising therapeutic target for the pharmacological modulation of the inflammatory and fibrogenic processes leading to NASH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Schwabl et al, using another sGC stimulator (riociguat), described reductions in portal hypertension and liver fibrosis in cholestatic (bile duct ligation) and toxic (carbon tetrachloride; CCl 4 ) models of cirrhosis in rats (4). More recently, Hall et al confirmed the antiinflammatory and antifibrotic effects of PRL in different murine models of NASH, including CCl 4 , streptozotocin plus a high-fat/high-cholesterol diet, and thioacetamide (5). Together, the findings of these studies position the cGMP pathway as a new and promising therapeutic target for the pharmacological modulation of the inflammatory and fibrogenic processes leading to NASH.…”
mentioning
confidence: 99%
“…Recently, we and others have demonstrated that modulation of cyclic guanosine-3′,5′-monophosphate (cGMP) exerts antiinflammatory and antifibrogenic effects in models of NASH and reduces portal pressure and fibrogenesis in cirrhotic rats (3)(4)(5). In these studies, small molecules with the ability to stimulate soluble guanylate cyclase (sGC), an enzyme that catalyzes the conversion of guanosine triphosphate (GTP) to cGMP, proved to be efficacious in the prevention as well as in the treatment of hepatic inflammation and fibrosis (3)(4)(5). In particular, using an optimized experimental model of NASH induced by a cholinedeficient L-amino acid-defined high-fat diet (CDAHFD) (6), we recently demonstrated that administration of the sGC stimulator praliciguat (PRL) delayed, in a dose-dependent manner, the development of liver inflammation and fibrosis (3).…”
mentioning
confidence: 99%
“…In our experiments we use hLiMTs generated in-vitro from human hepatic cells of healthy donors (3D Insight™ Human Liver Microtissues, InSphero AG, Switzerland) 14,15 . MTs are then exposed to different dietary regimes: a fasting diet is used to culture the livers in a lean state (as control), while a diabetic (fatty) diet induces steatosis (see Methods).…”
Section: Resultsmentioning
confidence: 99%
“…MTs have been introduced as a mean to simulate and probe disease conditions by allowing high throughput drug screening without need for biopsies of sick individuals, to better understand the mechanisms by which diseases operate and progress, and to reduce the need for animal testing, all of which could contribute to an accelerated development of new therapeutic treatments 1316 . In this study we focus on human liver MTs (hLiMTs), specifically treated to simulate non-alcoholic fatty liver disease (NAFLD) 14,15 . NAFLD has become a global medical issue for 10-40% of adults from different demographics worldwide, and the mechanisms by which this disease progresses still eludes researchers 17,18 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the anti‐inflammatory, antifibrotic, renoprotective, and hepatoprotective effects of praliciguat demonstrated in preclinical models, 7,13,14 emerging preclinical and clinical data indicate that praliciguat may have favorable effects on metabolic parameters, including cholesterol and insulin resistance 9,15,16 . These effects are of particular interest since, to our knowledge, they have not been reported for other sGC stimulators in humans and could be accentuated by the extensive tissue distribution of praliciguat.…”
Section: Discussionmentioning
confidence: 97%